Design of fractional order PDD controller for robotic arm using partial cancellation of non minimum phase zero - Manpreet Kaur; Swati Sondhi; Venkata Karteek Yanumula (Alexandria Engineering Journal)
In this paper, a two Degrees of freedom manipulator in the form of Quanser QUBE-Servo 2 system is used. It is an unstable system having non-minimum phase with right half s-plane pole and zero. The conventional controllers did not achieve the loop robustness for these types of systems. In this work, a Fractional-order proportional derivative (FOPDD) controller is proposed for the system whose mathematical model is made up of two loops where inner and outer loops are used for pendulum and rotary arm position respectively. The method of partial cancellation having a pre-compensator is used for non-minimum phase zeros of the system. Further, the parameters are selected using global stability region plots in which the stability of the system is shown using Riemann surface. The integral error criterion including Integral Absolute Error (IAE), Integral Square Error (ISE) and Integral Time Absolute Error (ITAE); and other performance metrics such as rise time, settling time, overshoot and undershoot are used to compare the robustness of the controllers under nominal environment, trajectory tracking and external disturbances. The simulation results indicate that the proposed FOPDD controller outperforms other existing controllers in terms of performance specifications which further justifies its usage in real-time applications.